Factors Affecting Financial Stability Planning for Retirement A Case Study on Customer of UOB Bank, Sriwara Branch - Samakkadkarn, Wimonporn; Srising, Panya (Arts of Management Journal, 2020)
The objectives of this study were 1) to study pattern of financial stability planning for retirement; 2) to investigate the level of importance of financial stability planning; 3) to examine the factors affecting financial stability planning. The research applied the study framework from 2010 Thailand Securities Institute (TSI) Capital Market Development Fund (CMDF), The Stock Exchange of Thailand (SET). This quantitative research applied questionnaire as a research tool for collecting data from the sample group. The target group was 400 customers of UOB Bank, Sriwara Branch. The sample size was calculated based on Yamane’s formula with a confidence coefficient of 95%. Data were analyzed through descriptive statistics comprising percentage, mean, Standard Deviation, T-test statistic, One-Way ANOVA, Multiple Correlation with a given statistical significance level of 0.05. The results demonstrated that most of the respondents were female whose age between 41 -50 years old, marital status, average degree as a bachelor, working as private company officers with an average monthly income of 25,001-35,000 THB. Economic status was the most important factor followed by the knowledge and understanding of financial planning. The least important factor was information perception. The study also revealed that 1) the perception of the importance of financial stability planning for retirement was considered as high level; 2) customers of UOB Bank, Sriwara Branch with different marital status had different patterns of financial planning; and 3) factor that can forecast factors affecting financial planning was knowledge, understanding of financial planning and economic status. To conclude, pattern of financial planning for retirement influenced by economic fluctuations. In addition, marital status affects patterns of financial planning for retirement.